Green pharmacy practice – a multi method study of environmental sustainability measures implemented in Swedish pharmacies - Elin Salehi; Christina Ljungberg Persson; Helle Håkonsen (Journal of Pharmaceutical Policy and Practice)
Background: Community pharmacies have an important role to play in green pharmacy practice. As Sweden has been recognised as a driving force in environmental initiatives in the pharmaceutical sector, the aim of this study was to investigate how environmental sustainability is addressed at company and local level in Swedish pharmacies.Methods: Using a multi-method approach, we reviewed written material from Swedish pharmacy chains and conducted a survey among community pharmacists. The written material consisted of sustainability reports and responses to email inquiries, answered by the companies’ sustainability managers in March 2022. A total of 269 pharmacists responded to the survey, divided into two survey rounds, one in April 2021 and one in November/December 2023. The survey was conducted digitally and disseminated via the chains.Results: The study identified 24 environmental sustainability measures, whereof three were in force across all pharmacy chains. Key measures were prescription reviews to reduce dispensing of unnecessary medications, management of medical waste from households (mandatory), and fossil-free deliveries. A large majority of the participants reported that providing information on proper medicine use and waste management were part of their daily work. There was a significant change in practice regarding the dispensing of only the amount necessary for the customer's dosing regimen and the sale of plastic bags from 2021 to 2023. Notably, Swedish pharmacies implemented a label for over-the-counter medicines in 2021 that indicates whether the manufacturer is transparent about its manufacturing procedures. However, the survey showed that pharmacists had limited knowledge of what this label meant not only when it was introduced, but also two years later.Conclusion: Swedish pharmacy chains have made significant progress in implementing sustainability measures. However, there is room for improvement in terms of pharmacists’ awareness of the sector's own environmental initiatives and better integration of measures outlined at company level into pharmacy practice.